Automated regulation of hemodynamic variables. - Rao, R.R (IEEE Engineering in medicine and biology magazine)
Experimental studies of two control methodologies for regulating multiple variables in critical care patients are described. The control strategies for the regulation of mean arterial pressure and cardiac output use vasoactive and inotropic drugs. Corresponding experimental results from the evaluation of the controllers with canines are presented.